The effects of pension reforms on physician labour supply: Evidence from the English NHS - Carol Propper; George Stoye; Max Warner (Institute for Fiscal Studies (IFS), 2023)
We examine the labour supply response of senior doctors in England following a reform of the public sector pension system that moved employees from a final salary to a career average pension plan. Exploiting the staggered rollout of the reform across narrowly defined age groups, we find that doctors increased labour supply by just under 4% four years after exposure. This implies a labour supply elasticity with respect to pension wealth of -0.05, and with respect to current returns to work of 0.04. This indicates doctors' responses were small despite relatively large changes in financial wealth induced by the reforms.
Keywords: H55; J22; J26; I10; 330; Doctor labour supply; Labour supply elasticity; Defined Benefit pensions; Public pension reform